Simulative Model of Integrated Security System - Zilys, M.; Valinevicius, A. (Elektronika ir Elektrotechnika, 2001)
The motivation to write this work was induced by the need to evaluate the parameters of security systems, to analyze in detail the processes, which occur in security system evaluation and suggest the possible ways of their optimization. Nowadays the standpoint of evaluating security systems efficiency is rather limited. The systems are evaluated only according to the efficiency of elements, which make up the system and their number. Without considering the global system’s parameters (the response time, algorithm of strategy choice, the intensity of the events stream, intrusion time) the security system, even if it consists of the most efficient equipment might be not effective.The experimental influence stream analysis of integrated security system was conducted. The integrated security system model which uses the real accumulated experimental event arrays, allows to simulate the processes which occur in the real security system, modify the loading of the response stream and foresee the possibility of the next intrusion as well as to arrange the response team properly.